Compound odontoma associated with impacted maxillary central incisor dictates a need to be vigilant to canine eruption pattern: A 2-year follow-up - Shilpy Singla; Sachin Gupta (Wolters Kluwer Medknow Publications, 2016)
Canine deviation from its path of eruption is usually followed by either delayed or impaction of canine. One of the important and not so noticed reasons for canine displacement is formerly impacted central incisor. The difference in age of eruption of these two teeth is 4 years; however, the absence of maxillary incisor should be perceived with utmost conviction about impending canine displacement leading to its impaction as well. This case presents similar picture where composite, compound odontoma with respect to maxillary central incisor led to its impaction resulted in deviated path of eruption for erupting canine. This canine displacement to worsen prognosis ended up getting impacted if not dealt with cautiously in the later stages of occlusal development.